Parental experiences of using continuous glucose monitoring in their young children with early-stage type 1 diabetes: a qualitative interview study - Roberts, Alison G.; Tully, Alexandra S.; Binkowski, Sabrina K.; Bebbington, Keely R.; Penno, Megan A. S.; Anderson, Amanda J.; Craig, Maria E.; Colman, Peter G.; Huynh, Tony; McGorm, Kelly J.; Soldatos, Georgia; Vuillermin, Peter J.; et al. (Frontiers in Clinical Diabetes and Healthcare, 2024)
AimTo explore parents’ experiences of using continuous glucose monitoring (CGM) in their young children with early-stage type 1 diabetes, being followed in the Australian Environmental Determinants of Islet Autoimmunity (ENDIA) study.MethodsParents of children with persistent islet autoimmunity who enrolled in the ENDIA CGM sub-study were invited to participate in an optional interview. Semi-structured phone interviews were conducted by a single researcher using an interview guide developed by a multi-disciplinary team. Interviews were conducted following a single CGM monitoring period and prior to parents receiving feedback on their child’s glycemic status. Following transcription, thematic analysis was conducted to determine common themes.ResultsNine parents (8 mothers, 1 father) were interviewed corresponding to ten children, with a mean (SD) age of 5.6 (2.2) years, who wore CGM for 97 (0.1)% of the time during their monitoring period. Three main themes were identified: (1) Information empowers and helps to reduce uncertainty; (2) Families’ acceptance of using CGM; and (3) Involvement in research provides support and preparation for the unknown.ConclusionsParents reported a positive experience of their young child wearing blinded CGM, and the children tolerated wearing CGM very well. Parents were empowered by knowing they would receive information on their child’s glucose levels and patterns and felt well supported. This study provides novel insights into parents’ experiences of using CGM in very young children with early-stage type 1 diabetes.